A “Notification” on The Use of Social Media as A Means of Community Resilience in Crisis Management - Çerçi, Ümmü Özlem (Journal of Communication and Public Relations, 2024)
This comparative study explores the role of social media in building community resilience during the Covid-19 pandemic, focusing on citizens' communication habits. Community resilience, defined as the ability to withstand, adapt, and recover from adverse situations, is crucial, especially in the face of crises like pandemics. Effective strategic communication with the target audience is vital for creating and maintaining community resilience. Strategic communication plays a key role in helping communities prepare, respond, and recover by providing clear information, encouraging cooperation, and fostering adaptable behaviors. In the digital age, where a significant portion of the population lives online, social media platforms serve as essential tools for collecting information, disseminating crisis-related news, mobilizing the audience, and contributing to crisis management efforts. This study, conducted between May 5-10, 2020, with 800 participants from Turkey and 800 from the USA, reveals that individuals in both countries spend a considerable amount of time online, utilizing at least 3-4 social media applications. Instagram, YouTube, Facebook, and Twitter are identified as popular platforms. Most importantly, both Turkey and the United States demonstrate resilient societies, and there is a significant correlation between community resilience and the use of social media for obtaining information during the Covid-19 crisis. This emphasizes the critical role of crisis communication as a key success factor in building community resilience.